Evidence for Prepulse Inhibition of Visually Evoked Motor Response in Drosophila melanogaster - Helgi B. Schiöth; Laura Donzelli; Nicklas Arvidsson; Michael J. Williams; Thiago C. Moulin (Biology, 2023)
Prepulse inhibition (PPI) is a widely investigated behavior to study the mechanisms of disorders such as anxiety, schizophrenia, and bipolar mania. PPI has been observed across various vertebrate and invertebrate species; however, it has not yet been reported in adult Drosophila melanogaster. In this study, we describe the first detection of PPI of visually evoked locomotor arousal in flies. To validate our findings, we demonstrate that PPI in Drosophila can be partially reverted by the N-methyl D-aspartate (NMDA) receptor antagonist MK-801, known for inducing sensorimotor gating deficits in rodent models. Additionally, we show that the visually evoked response can be inhibited by multiple stimuli presentation, which can also be affected by MK-801. Given the versatility of Drosophila as a model organism for genetic screening and analysis, our results suggest that high-throughput behavioral screenings of adult flies can become a valuable tool for investigating the mechanisms behind PPI.